2023
DOI: 10.1101/2023.03.06.23286584
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Relapse timing is associated with distinct evolutionary dynamics in DLBCL

Abstract: Diffuse large B-cell lymphoma (DLBCL) is cured in over 60% of patients, but outcomes are poor for patients with relapsed or refractory disease (rrDLBCL). Here, we performed whole genome/exome sequencing (WGS/WES) on tumors from 73 serially-biopsied patients with rrDLBCL. Based on the observation that outcomes to salvage therapy/autologous stem cell transplantation are related to time-to-relapse, we stratified patients into groups according to relapse timing to explore the relationship to genetic divergence and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
0
0
Order By: Relevance
“…Virtual trials were also used to calculated the statistical power of real trials, not based on an aspirational hazard ratio, but using a data-based prediction of hazard ratio, and correctly predicted that only RCHP-polatuzumab-vedotin and RCHOP-tucidinostat were likely to be significantly superior to RCHOP ( Figure 4D ). Our model does not reproduce the incidence of relapses later than 3 years, but recent genomic studies have found that ‘late relapses’ of DLBCL usually result from cancer precursor cells acquiring new mutations to develop into related yet de novo cases of DLBCL (55). Thus, the inability of our model to reproduce late relapses supports the theory that late relapses are effectively new and chemotherapy-naïve lymphomas.…”
Section: Discussionmentioning
confidence: 98%
“…Virtual trials were also used to calculated the statistical power of real trials, not based on an aspirational hazard ratio, but using a data-based prediction of hazard ratio, and correctly predicted that only RCHP-polatuzumab-vedotin and RCHOP-tucidinostat were likely to be significantly superior to RCHOP ( Figure 4D ). Our model does not reproduce the incidence of relapses later than 3 years, but recent genomic studies have found that ‘late relapses’ of DLBCL usually result from cancer precursor cells acquiring new mutations to develop into related yet de novo cases of DLBCL (55). Thus, the inability of our model to reproduce late relapses supports the theory that late relapses are effectively new and chemotherapy-naïve lymphomas.…”
Section: Discussionmentioning
confidence: 98%